2020
DOI: 10.1177/1077559520947816
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Abusive Parenting: Role of Prospective Maternal Distress and Family Violence

Abstract: Parents who were abused as children are at increased risk for perpetuating maladaptive parenting practices, yet the mechanisms underlying this relationship remain unclear. This study prospectively examined maternal distress (a latent variable consisting of depressive symptoms and daily stress) and family violence as potential mediators in the intergenerational transmission of abusive (i.e., psychologically aggressive and physically assaultive) parenting. Participants included ( N = 768) mother-child dyads iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The present findings support our first hypothesis, as depression emerged as a risk factor and parent–child connectedness as a protective factor in the associations between parental maltreatment history and maltreatment in their child. Our findings are in line with those reported in studies from Burundi and other regions that have demonstrated a link between parental and offspring maltreatment experiences (Crombach & Bambonye, 2015; Morelli et al., 2021; Negriff et al., 2020). The present research also adds to the extant literature by highlighting the roles of depression and parent–child connectedness, which can facilitate clinical interventions.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings support our first hypothesis, as depression emerged as a risk factor and parent–child connectedness as a protective factor in the associations between parental maltreatment history and maltreatment in their child. Our findings are in line with those reported in studies from Burundi and other regions that have demonstrated a link between parental and offspring maltreatment experiences (Crombach & Bambonye, 2015; Morelli et al., 2021; Negriff et al., 2020). The present research also adds to the extant literature by highlighting the roles of depression and parent–child connectedness, which can facilitate clinical interventions.…”
Section: Discussionsupporting
confidence: 92%
“…For example, caregivers of adolescents in poverty are more likely to have irregular work schedules contributing to reduced parental monitoring (Hsueh & Yoshikawa, 2007). Poverty also exacerbates risk through parental stress which may influence negative parent–child interactions, experiences that are highly predictive of children’s conduct problems (Morelli et al, 2020). Poverty represents a perilous context that increases risk for the adverse outcomes explored in this study, both directly and indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate the high likelihood of intergenerational transmission of risky parenting styles (Madigan et al, 2019). This suggests that a child's biological parents' harsh, aggressive, and/or neglectful parenting behaviors may be transmitted from grandparents' similar parenting style via some pathways, such as the parent's mental distress (Morelli et al, 2020). In terms of other significant predictors, we found that children living in households with licensed kinship caregivers were at a higher risk of neglect, and this might be because licensed kinship families were more economically vulnerable.…”
Section: Discussionmentioning
confidence: 99%